Design of a Compact Tuning Fork-Shaped Notched Ultrawideband Antenna for Wireless Communication Application - M. N. Shakib; M. Moghavvemi; W. N. L. Mahadi (The Scientific World Journal)
A new compact planar notched ultrawideband (UWB) antenna is designed for wireless communication application. The proposed antenna has a compact size of 0.182λ × 0.228λ × 0.018λ where λ is the wavelength of the lowest operating frequency. The antenna is comprised of rectangular radiating patch, ground plane, and an arc-shaped strip in between radiating patch and feed line. By introducing a new Tuning Fork-shaped notch in the radiating plane, a stopband is obtained. The antenna is tested and measured. The measured result indicated that fabricated antenna has achieved a wide bandwidth of 4.33–13.8 GHz (at −10 dB return loss) with a rejection frequency band of 5.28–6.97 GHz (WiMAX, WLAN, and C-band). The effects of the parameters of the antenna are discussed. The experiment results demonstrate that the proposed antenna can well meet the requirement for the UWB communication in spite of its compactness and small size.